Pensonic Holding Berhad Strategies To Achieve Competitiveness - Lim, Peng Boon (2005)
The Pensonic Holdings Bhd (PHB) Group had its beginning in Keat Radio & Electrical Co, a sole proprietor business and retailer in electrical and elecvtronic appliances based in Balik Pulau, Penang.